Near-Infrared Activatable Phthalocyanine–Poly-L-Glutamic Acid Conjugate: Enhanced in Vivo Safety and Antitumor Efficacy toward an Effective Photodynamic Cancer Therapy - Cheah, Hoay Yan; Gallon, Elena; Dumoulin, Fabienne; Hoe, See Ziau; Japundžić-Žigon, Nina; Glumac, Sofija; Lee, Hong Boon; Anand, Prem; Chung, Lip Yong; Vicent, Maria Jesus; Kiew, Lik Voon (American Chemical Society, 2018)
We previously developed a new zinc(II) phthalocyanine (ZnPc) derivative (Pc 1) conjugated to poly-L-glutamic acid (PGA) (1-PG) to address the limitations of ZnPc as part of an antitumor photodynamic therapy approach, which include hydrophobicity, phototoxicity, and nonselectivity in biodistribution and tumor targeting. During this study, we discovered that 1-PG possessed high near-infrared (NIR) light absorptivity (λ max = 675 nm), good singlet oxygen generation efficiency in an aqueous environment, and enhanced photocytotoxic efficacy and cancer cell uptake in vitro. In the current study, we discovered that 1-PG accumulated in 4T1 mouse mammary tumors, with a retention time of up to 48 h. Furthermore, as part of an antitumor PDT, low dose 1-PG (2 mg of Pc 1 equivalent/kg) induced a greater tumor volume reduction (-74 ± 5%) when compared to high dose ZnPc (8 mg/kg, -50 ± 12%). At higher treatment doses (8 mg of Pc 1 equivalent/kg), 1-PG reduced tumor volume maximally (-91 ± 6%) and suppressed tumor size to a minimal level for up to 15 days. The kidney, liver, and lungs of the mice treated with 1-PG (both low and high doses) were free from 4T1 tumor metastasis at the end of the study. Telemetry-spectral-echocardiography studies also revealed that PGA (65 mg/kg) produced insignificant changes to the cardiovascular physiology of Wistar-Kyoto rats when administered in vivo. Results indicate that PGA displays an excellent cardiovascular safety profile, underlining its suitability for application as a nanodrug carrier in vivo. These current findings indicate the potential of 1-PG as a useful photosensitizer candidate for clinical PDT.